Leadership of entrepreneurship at the macro level in South Africa - Mabusela, Onneile Ipeleng (My University, 2018)
The purpose of the study is to assess the state of leadership in entrepreneurship at the macro level in South Africa. This is further explored by assessing the gaps, issues and challenges and effectiveness of leadership as well as the roles of government and the private sector in entrepreneurship leadership. A qualitative methodology was incorporated through structured interviews with several South African entrepreneurs. The research finds that entrepreneurship in South Africa is not effectively led. Several initiatives from the private and public sector exist to support entrepreneurs but remain largely uncoordinated. There are a lack of standards and benchmarking at macro level even though entrepreneurs could benefit from guidelines, governance and strategy frameworks. Government does not understand or communicate with to entrepreneurs sufficiently. The private sector does not have the best interests of entrepreneurs at heart due to competing interests for clients with regards to markets. Incubators, accelerators and universities compete among themselves for funding and accolades which hinders their assistance to entrepreneurs. The negative culture in entrepreneurship, which permeates all aspects, needs to be improved through effective leadership the by enhancing the brand and knowledge of entrepreneurship throughout society. v Entrepreneurship needs to lead itself and educate other stakeholders through a unified voice and servant leadership in order to be led effectively at the macro level. Private Public Partnerships have the foundation for better entrepreneurship leadership at the macro level. Further research could include assessing how strong institutions are formed and how that can be applied to entrepreneurship, the needs and agendas of each stakeholder in entrepreneurship as well as the issues and challenges related to creating standards and benchmarks for entrepreneurship.
MBA
Keywords: Entrepreneurship -- South Africa. Leadership -- South Africa. Management.